Exploring mindfulness interventions across cultures: a comparative meta-analysis of mindfulness interventions for athletes in Western and Eastern contexts - Du, Senyao; Ning, Ziheng (Frontiers in Psychology, 2024)
Objective Applying mindfulness training across cultures can be challenging because its internal motivation depends on values, but there are differences between Western and Eastern contexts. This meta-analysis examines the comparative impacts of the Western Mindfulness-Acceptance-Commitment (MAC) approach and the culturally-adapted Chinese Mindfulness-Acceptance-Insight-Commitment (MAIC) mindfulness training for athletes, to explore the importance of cultural adaptation in cross-cultural psychology to psychological skills training. Methods This meta-analysis was registered with Prospero (ID: CRD42023474474) and adhered to the PRISMA principles. The PICO search methodology was employed to identify pertinent Chinese and English literature across six databases (Web of Science, PubMed, Scopus, CNKI, Wanfang, and VIP) from 2003 to 2023. The evidence originated from randomized controlled trials. Effect sizes were evaluated across three primary domains: athletic performance, mindfulness, and psychological flexibility, and heterogeneity and publication bias. Results Both MAC and MAIC demonstrated positive effects across all outcome categories in 18 studies. MAIC exhibited substantially larger effect sizes compared to MAC. In mindfulness (MAIC: g = 1.273, p < 0.001; MAC: g = 0.521, p = 0.001), sports performance (MAIC: g = 0.945, p = 0.015; MAC: g = 0.550, p < 0.001), MAC did not provide evidence of improved psychological flexibility (g = 0.076, p = 0.747), while MAIC demonstrated significant benefits (g = 0.964, p < 0.001). Discussion While MAIC is based on MAC, it yields more significant outcomes. This may be the “Insight” component introduced by MAIC, which skillfully integrates Eastern context. The MAIC strategy not only becomes more appropriate for local athletes but also indirectly enhances their mindfulness, athletic performance, and psychological flexibility, resulting from cultural adaptation. The new idea not only solves the culture shock caused by the direct application of Western MAC approach on Chinese athletes, but also provides a new solution to the problem that there is insufficient evidence to support the effect of the MAC approach on “psychological flexibility.” Investigating differential effects between MAC and MAIC contributes to understanding the significance of culturally adapting mindfulness training and transnational movement of practices. The findings will assist practitioners in selecting evidence-based protocols tailored to athlete needs and cultural contexts. Systematic review registration Prospero (ID: CRD42023474474).